Stabilising Peptoid Helices Using Non‐Chiral Fluoroalkyl Monomers. Issue 33 (27th June 2018) - Gimenez, Diana; Aguilar, Juan A.; Bromley, Elizabeth H. C.; Cobb, Steven L.
Abstract: Stability towards protease degradation combined with modular synthesis has made peptoids of considerable interest in the fields of chemical biology, medicine, and biomaterials. Given their tertiary amide backbone, peptoids lack the capacity to hydrogen‐bond, and as such, controlling secondary structure can be challenging. The incorporation of bulky, charged, or chiral aromatic monomers can be used to control conformation but such building blocks limit applications in many areas. Through NMR and X‐ray analysis we demonstrate that non‐chiral neutral fluoroalkyl monomers can be used to influence the Kcis/trans equilibria of peptoid amide bonds in model systems. The cis ‐isomer preference displayed is highly unprecedented given that neither chirality nor charge is used to control the peptoid amide conformation. The application of our fluoroalkyl monomers in the design of a series of linear peptoid oligomers that exhibit stable helical structures is also reported. Abstract : On the same side : NMR spectroscopy and X‐ray analysis were applied to demonstrate that non‐chiral, neutral fluoroalkyl monomers can be used to promote enhanced levels of cis ‐amide preference in model peptoid systems. These fluoroalkyl monomers were also directly applied to design a series of peptoid oligomers that exhibit stable helical structures, as shown by CD spectroscopy.